Development of a novel encystment medium: Enhancing diagnostic potential of Acanthamoeba spp. - Julalak Chuprom; Suthinee Sangkanu; Watcharapong Mitsuwan; Rachasak Boonhok; Alok K. Paul; Sonia M. Rodrigues Oliveira; Maria L. Pereira; Tajudeen O. Jimoh; Mohammed Rahmatullah; Polrat Wilairatana; Christophe Wiart; Ajoy K. Verma; et al. (National library of medicine, 2025)
Background and Aim: Acanthamoeba spp. are pathogenic microorganisms linked to severe infections in humans and animals, requiring a deeper understanding of their encystation process for effective diagnostics and research. This study focused on developing a novel encystment medium to induce synchronized encystation of Acanthamoeba spp. efficiently and rapidly. Materials and Methods: The study employed response surface methodology with a central composite design to optimize the encystment medium formulation. The key components included Tris-HCl, NaCl, glucose, and MgCl2 . The optimized liquid medium was spray-dried to produce a dehydrated powder for practical application. The encystation efficiency of different Acanthamoeba strains was assessed using hemocytometry and fluorescence microscopy. Results: The optimized medium, comprising 3.152 g/L Tris-HCl, 5.55 g/L NaCl, 8% (w/v) glucose, and 5.0 mM MgCl2 at pH 9.0, demonstrated exceptional encystation efficiency with rates ranging from 99% to 100%. A spray-dried powdered version of this medium was equally effective, achieving a 98.77% encystation rate for A. castellanii American Type Culture Collection 50739 in glucose-free conditions. Notably, optimal glucose concentrations varied among Acanthamoeba strains, with certain strains reaching maximum encystation at 6–8% glucose. Conclusion: This study successfully developed an innovative encystment medium that promotes rapid and efficient cyst production in Acanthamoeba spp. The medium enhances laboratory research and diagnostic capabilities, paving the way for future advancements in understanding and managing Acanthamoeba infections.